Model for Optimizing Land Use to Support Sustainable Environmental Economic Strengthening in the Upper Kampar River Basin - Nurdin; Suprayogi, Imam; Ermiyati; Audah, Syafridatul; Zaim, Zaflis (UIR PRESS, 2023)
Simple and complex agroforestry systems can be implemented simultaneously in the cultivation area within the Upper Kampar River Basin. Based on the ArcSWAT simulation results, the surface runoff (Qsurf) was estimated to be 37.20 mm, which is significantly lower than the existing land use runoff in 2014, which was 102.12 mm. This forms the basis for implementing simple agroforestry and complex agroforestry systems in the Upper Kampar River Basin. The plant species that can support these agroforestry systems are selected based on the principles of land conservation and the suitability of local plants in the Upper Kampar Watershed environment. Four types of filler plants are considered: coffee and cocoa for the simple agroforestry system, and gambier and ambon bananas/kepok bananas for the complex agroforestry system. These plant species are the most dominant filler plants in the Upper Kampar Watershed. To optimize the land with these filler plant species, analysis is conducted using Quantitative Methods (QM) for Windows 4 software based on objective functions and constraint functions. The analysis determines that coffee is suitable for the simple agroforestry system, while gambier is suitable for the complex agroforestry system. Before land optimization with the planting of coffee, cocoa, gambier, and ambon bananas/kepok bananas, the net profit is estimated to be IDR. 359,113,963,811.06. After optimizing the land and developing it with the suitable filler plant species, only coffee and gambier are planted, while cocoa and ambon bananas/kepok bananas are planted according to the available area. As a result, the net profit increases to IDR. 951,426,300,000, with an economic value increase of IDR. 592,312,336,188.94 per year.